The End of China's One‐Child Policy. Issue 1 (March 2016) - Feng, Wang; Gu, Baochang; Cai, Yong
Abstract : Starting on January 1, 2016, all Chinese couples are allowed to have two children. This marks the end of China's one‐child policy, which has restricted the majority of Chinese families to only one child for the last 35 years. Yet, China's policy change came at least a decade later than it should have. The costly lessons to be learned are not only in politics and public policymaking, but also in how parts of the academic community informed and misinformed public policymaking.